Realising the rhetoric: refreshing public health providers' efforts to honour Te Tiriti o Waitangi in New Zealand. Issue 2 (4th March 2017) - Came, H. A.; McCreanor, T.; Doole, C.; Simpson, T.
ABSTRACT: Objectives. New Zealand has a unique tool, Te Tiriti o Waitangi, the Treaty of Waitangi, for addressing health disparities. Indigenous Māori have compromised health status compared to other groups. This paper investigates ways in which public health units (PHUs) and non-governmental organisations (NGOs) use Te Tiriti o Waitangi in service delivery to Māori. Design. A nationwide telephone survey of primary health providers ( n =162) was conducted in 2014-15. Participants were asked about effectiveness and monitoring of their service delivery to Māori. Results. PHUs reported actively working with Māori, and Te Tiriti o Waitangi to reduce health disparities. Direct Māori engagement with development and delivery of programmes was viewed as essential. Strategies included designated PHU staff in positions of responsibility, formal partnerships with Māori, and providing operational and strategic guidance. Some PHUs supported development of cultural competencies. NGO responsiveness to Māori was variable. Some NGOs described prioritising service delivery and programmes for Māori. Others reported the focus of their service was European or other non-Māori ethnicities. Lack of resources or past difficulties engaging with Māori were barriers. Conclusion. Public health has an ethical commitment to reduce health disparities. Advancing Te Tiriti obligations in everyday practice has the potential to address inequalities.